PENINGKATAN KEMAMPUAN MOTORIK KASAR MELALUI PERMAINAN LOMPAT TALI PADA ANAK USIA 5-6 TAHUN - Oliva, Oliva; Ali, Muhammad; Halida, Halida (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractWhat is used is what can be done to overcome the problem of gross motor skills and strength in children. Problems that occur in the child's ability to jump. Outdoor games are underutilized by teachers to do gross motor activities outside, teachers do more gross motor activities in the classroom. Children who often do it themselves outside of class, teachers rarely talk with children to develop strength and balance.Jump rope activities can increase the strength and speed of leg muscles, improve body flexibility and balance, and develop coordination of the eyes, arms, and legs. Based on the above observations, the researchers are interested in conducting a Class Action research entitled The Ability of Rough Motoric Ability of Children 5-6 Years in Pontianak City Sister Kindergarten..Keywords: Rough Motor, Jump Rope